A huge Ewing's sarcoma of the rib presenting with superior vena cava syndrome and dysphagia. Issue 11 (21st April 2022) - Lin, Dan; Zhu, Xiaomu; Tian, Long; Qin, Changlong; Dong, Jingsi; Zhou, Qinghua
Abstract: A 24‐year‐old male patient was admitted to our center complaining of dizziness (superior vena cava syndrome [SVCS]), dysphagia and pain in the right chest wall. At the initial diagnosis, the patient had been found to have an irregular shaped 35 × 30 × 27 cm mass in the right side of his chest. On November 12, 2019, this patient received surgery in our center. The right sixth rib and the tumor were completely removed (R0), while preserving all the lung tissue and other organs in the chest. The patient recovered well after surgery, and his right lung was fully expanded. Abstract : A 24‐year‐old male presenting with superior vena cava syndrome was diagnosed with a huge Ewing's sarcoma of the right rib. On November 12, 2019, this patient received surgery and the right sixth rib and the tumor were completely removed (R0), while preserving all the lung tissue and other organs in the chest. The patient recovered well after surgery and had no recurrence after 3 years.